Augmented reality-based evacuation simulation to study crowd behaviors - Muhamad Nizam, Muhamad Adli; Mohd Ibrahim, Azhar (IAEME Publication, 2020)
To date, it has been especially challenging to correlate progress in human behavior education in emergencies with complicated dynamics of crowd behavior particularly during evacuation. Previous research does not explore deeply the effect of different crowd behaviors and the evacuation scenarios. This study proposes the uses of AR as a tool to analyze the effect of an aggressive and passive agent on the evacuation time. The focus here is on the modeling of the AR-based crowd evacuation, agents’ behaviors and analysis of the simulation. From the result, it is observed that the increasing aggressive agents decreases the evacuation time. This is because their acceleration is slightly higher compared to the patient agents.